Toxic prey [large type] - Sandford, John, 1944 February 23- (Sandford, John, 1944 February 23- Prey novel, 2024)
When a renowned expert in infectious diseases disappears without a trace, Letty Davenport, with the world on high alert, calls in her father, Lucas, to locate him, and when their worst fears are confirmed, they must race against time to stop the virus he created from becoming the perfect weapon.